Case series demonstrating the value of computed tomography perfusion in differentiating ischemic strokes from seizures in patients with isolated aphasia - Victoria Serven; Jonathan D. Clemente; Andrew W. Asimos (Journal of the American College of Emergency Physicians Open)
Abstract The value of computed tomography perfusion (CTP) imaging in suspected stroke patients who are not candidates for mechanical thrombectomy is promising. This case series demonstrates how CTP imaging aided in distinguishing seizure from stroke in 5 patients who presented to the emergency department with acute onset of isolated aphasia.